2008
DOI: 10.1111/j.1467-2979.2007.00265.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing catch‐and‐release science with biotelemetry

Abstract: Introduction 80Traditional C&R research methods 81Quantitative overview of biotelemetry in C&R science 82Abstract Catch-and-release (C&R) angling is widely practised by anglers and is a common fisheries management strategy or is a by-product of harvest regulations. Accordingly, there is a growing body of research that examines not only the mortality associated with C&R, but also the sublethal physiological and behavioural consequences. Biotelemetry offers a powerful means of remotely monitoring the behaviour, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
118
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 144 publications
(124 citation statements)
references
References 94 publications
2
118
2
Order By: Relevance
“…Sharks that swallow hooks are likely to suffer a shortened lifespan and reduced reproductive output as ingested hooks cause serious disease and may result in long-term mortality (Borucinska et al 2002;Donaldson et al 2008). In the current study, only 32 sharks (3.4%) showed evidence of internalised fishing gear, with fishing line trailing from the mouth, gill-slits or cloaca.…”
Section: Discussionmentioning
confidence: 99%
“…Sharks that swallow hooks are likely to suffer a shortened lifespan and reduced reproductive output as ingested hooks cause serious disease and may result in long-term mortality (Borucinska et al 2002;Donaldson et al 2008). In the current study, only 32 sharks (3.4%) showed evidence of internalised fishing gear, with fishing line trailing from the mouth, gill-slits or cloaca.…”
Section: Discussionmentioning
confidence: 99%
“…There is a growing interest in advancing our understanding of the fate of animals released from fishing gears (Davis 2002;Broadhurst et al 2006;Donaldson et al 2008;Davis 2010). By comparing fishing techniques, handling practices, and environmental variables with postrelease outcomes (Davis 2002), research can inform management efforts to reduce or account for postrelease mortality (e.g., Huse and Vold 2010;Gale et al 2011;Roberts et al 2011;Baker et al unpublished data) or improve animal welfare (e.g., Butcher et al 2011).…”
Section: Spawning Salmon Resilience To Capture 525mentioning
confidence: 99%
“…Since there were low river dropout and low post net-release mortality rates, the telemetry data provide valuable support for confidence in the T-bar tag estimates of exploitation rate and thus of fisheries management advice relating to the fishery. Telemetry data such as these provide an increasingly important complementary role in facilitating fisheries stock assessment, management and conservation (Clarke et al, 1991;Webb, 1998;Erkinaro et al, 1999;Donaldson et al, 2008). Our study found that later running Atlantic salmon predominantly used the lower to middle sections of the main Tweed as an assumed spawning area.…”
Section: Discussionmentioning
confidence: 53%